A Mechanism for Tectonic Inheritance at Transform Faults of the Iapetan Margin of Laurentia - Thomas, William (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
Transform faults along the Iapetan rifted continental margin of Laurentia offset the continental rift and/or bound domains of oppositely dipping lowangle detachments. Rift-parallel and transform-parallel intracratonic fault systems extend into continental crust inboard from the rifted margin. Ages of synrift igneous rocks, ranging from 765 to 530 Ma, document non-systematic diachroneity of rifting along the Iapetan margin. Synrift sedimentary accumulations show abrupt variations in thickness across transform faults, and some concentrations of synrift igneous rocks are distributed along transform faults and transform-parallel intracratonic fault systems. The greatest thicknesses of Cambrian–Ordovician passive-margin shelf-carbonate deposits are along transform margins and in continental-margin basins along transform faults, as well as along transform- parallel intracratonic fault systems, indicating anomalously great post-rift thermal subsidence along transform faults. Along the Ordovician– Permian Appalachian-Ouachita orogenic belt, a diachronous array of synorogenic clastic wedges fills foreland basins, recording tectonic-loaddriven flexural subsidence of the lithosphere. The greatest thicknesses of synorogenic clastic wedges of all ages are consistently in foreland basins along transform margins and inboard from intersections of transform faults with the rifted margin, indicating systematically weaker lithosphere along transform faults. The distinctive and pervasive properties and behaviour of the lithosphere along transform faults in successive tectonic settings suggest fundamental controls on tectonic inheritance at transform faults. Recent models for continental rifting incorporate ductile extension of the mantle lithosphere beneath brittle extension of the crust; the domain of ductile extension of the mantle lithosphere may reach significantly inboard from the rifted margin of the brittle crust, accounting for rift-parallel extensional faults in the crust inboard from the rifted margin. A transform offset of a rift in brittle crust requires a similar offset in ductile extension of the mantle lithosphere, leading to differential ductile flow on opposite sides of the transform and imparting a transformparallel distributed-shear fabric. Transform- parallel distributed shear in the mantle lithosphere provides a mechanism for brittle transform-parallel fault systems in the continental crust. Studies of seismic anisotropy show fast directions parallel with transform faults, indicating systematic orientation of crystals through transform-parallel distributed shear in the mantle lithosphere.